Insights Into Subduction‐Zone Fluid‐Rock Interactions and Carbon Cycling From Magnesium Isotopes of Subducted Ophiolitic Mélanges in the Arabian‐Nubian Shield - Yuan‐Ru Qu; Sheng‐Ao Liu; Hamed Gamaleldien (Geochemistry, Geophysics, Geosystems)
Abstract Fluid‐rock interactions play an important role in element mobilization, mass transfer, and formation of critical metals in subduction zones. However, tracking the multistage fluid‐rock interactions within subduction channels remains elusive. Here we conducted bulk‐rock major and trace element and magnesium (Mg) isotopic analyses on a suite of subducted ophiolitic mélange rocks from Wadi Al Barramiyah in the Arabian‐Nubian Shield of the Eastern Desert (ED) of Egypt. The rock suite includes serpentinites, talc rocks, talc‐dolomite rocks, tremolite‐dominated schists, and marbles. Talc rocks are characterized by low MgO contents and high δ26MgDSM‐3 values (0.03–0.13‰) relative to serpentinites (−0.18‰), indicating the release of isotopically light fluid during the metasomatic replacement of antigorite by talc. Tremolite‐dominated schists and talc‐dolomite rocks display higher CaO contents and lower δ26Mg (−0.25‰ to −0.03‰ and −1.04‰ to −0.18‰, respectively) than those of talc rocks and serpentinites. These signatures, along with high CaO/Al2O3 and low Rb/Sr ratios, indicate infiltration of low‐δ26Mg carbonate‐rich fluids, supported by extremely low δ26Mg (down to −2.38‰) observed in nearby marbles. Our findings demonstrate that antigorite dehydration liberates substantial numbers of H2O‐rich fluids, facilitating the dissolution of carbonate minerals in marbles. Subsequent carbonate metasomatism effectively sequesters carbon from aqueous carbon‐bearing fluids, transforming silicate minerals into carbonates. These new results highlight the significant role of mélange rocks in the multistage fluid‐rock interactions and carbon recycling in subduction zones, offering valuable insights into mantle Mg isotopic heterogeneity and crust‐mantle interactions.